Notas cruzadas entre el Dr. Alfonso Uribe Misas y A. Restrepo Moreno - Restrepo Moreno, Alfonso; Uribe Misas, Alfonso (Estudios de Derecho, 1929)
Notas cruzadas entre el Dr. Alfonso Uribe Misas y A. Restrepo Moreno